Биофизические показатели ротовой жидкости и твердых тканей зубов у детей с ранним детским кариесом = Biophysical indices of oral liquid and hard tissue of teeth in children with early childhood caries - Victoriya Kovalchuk; Eduard Denga (Kazimierz Wielki University, 2015)
Kovalchuk V. V., Denga E. M. Биофизические показатели ротовой жидкости  и твердых тканей зубов у детей с ранним детским кариесом = Biophysical indices of oral liquid and hard tissue of teeth in children with early childhood caries. Journal of Education, Health and Sport. 2015;5(11):53-61. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33232 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A53-61 https://pbn.nauka.gov.pl/works/666327 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.09.2015. Revised 05.10.2015. Accepted: 30.10.2015.   УДК: 616.314-002−053.2/.6+616-039.71 UDC: 616.314-002−053.2/.6+616-039.71   БИОФИЗИЧЕСКИЕ ПОКАЗАТЕЛИ РОТОВОЙ ЖИДКОСТИ  И ТВЕРДЫХ ТКАНЕЙ ЗУБОВ У ДЕТЕЙ С РАННИМ ДЕТСКИМ КАРИЕСОМ   BIOPHYSICAL INDICES OF ORAL LIQUID AND HARD TISSUE OF TEETH IN CHILDREN WITH EARLY CHILDHOOD CARIES   В. В. Ковальчук, Э. М. Деньга V. V. Kovalchuk, E. M. Denga   ГУ «Институт стоматологии Национальной академии медицинских наук Украины» State establishment "The Institute of Stomatology of the National Academy of Medical Science of Ukraine"   Реферат Предложенная комплексная профилактика раннего детского кариеса, учитывающая сниженные возможности организма в этом возрасте, несовершенство иммунной и центральной нервной систем, практически отсутствие эндокринной системы, и поддерживающая их эффективно стабилизировала рН ротовой жидкости у детей 2-5 лет, нормализуя функциональные реакции, ответственные за гомеорезис, увеличивала кислоторезистентность эмали зубов, ее электрическое сопротивление и, следовательно, ее качество. Ключевые слова: ранний детский кариес, комплексная профилактика, ротовая жидкость, твердые ткани зубов.   V.V. Kovalchuk, E. M. Denga State establishment "The Institute of Stomatology of the National Academy of Medical Science of Ukraine" BIOPHYSICAL INDICES OF ORAL LIQUID AND HARD TISSUE OF TEETH IN CHILDREN WITH EARLY CHILDHOOD CARIES Abstract Early childhood caries is a multifactorial disease. In the works for the prevention of early childhood caries, usually focuses on oral health of children, the use of calcium, and fluorine-containing products, sealing fissures of molars, explanatory work with parents. At the same time the issue of reducing the body's capacity in early childhood, deficient immune and central nervous systems, the endocrine system is virtually absent, to support them in prevention activities with virtually no attention paid. The aim was to study the biophysical parameters of the oral liquid and hard tissue of teeth in children 2-5 yars of the western region of Ukraine with a reduced concentration of fluoride in drinking water in the process prevention of major dental diseases. Materials and methods. The study involved 58 children aged 2-3 and 4-5 years with early childhood caries of city Ternopil. The main groups of children received prophylactic complex developed in stages included the adaptogenic, antioxidant, membranotropic, prebiotic, anti-inflammatory and remineralizing agents. Results. Conclusions. The proposed integrated prevention of early childhood caries effectively stabilize the pH of oral liquid in children 2-5 years old, normalizing functional responses responsible for gomeorezis, increased acid resistance of tooth enamel, its electrical resistance and hence its quality. Keywords: early child caries, integrated prevention, oral liquid, hard tissue of teeth.